Implementation Of Social Protection Policy Through Program Keluarga Harapan (PKH) In Rural Society - Ade Ayu Murti Asih; Saif Askari; Trianah Shofiani (Asian Journal of Law and Humanity, 2022)
This paper analyzes about the implementation of the PKH program and the factors that influence the implementation of the program. This policy evaluation research uses a qualitative approach. Data obtained by observation, interviews, and documentation. The selection of informants used a purposive technique and was developed using the snowball method. The analysis technique uses an interactive model. The results of the study show that the implementation of PKH in North Wanarejan village is in accordance with the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning PKH. Supporting factors in the implementation of PKH include: 1) the enthusiasm of the residents in responding to the Program; 2) the presence of PKH recipients participating in activities; 3) active recipients of PKH assistance in implementing the program; 4) PKH recipients are easy to accept suggestions and directions from PKH facilitators. Meanwhile, the inhibiting factors in the implementation of PKH include: 1) the community does not understand the regulations related to the PKH mechanism; 2) the data received by the PKH facilitator is direct data from the central government, so the data is different from the facts on the ground; 3) The names of PKH participants who are not entitled to receive assistance cannot be exchanged, replaced or added. This fact contradicts the Regulation of the Minister of Social Affairs No. 1 of 2018 concerning PKH.